Insulin-like growth factor-1 induces regulatory T cell-mediated suppression of allergic contact dermatitis in mice - Bjarki Johannesson; Susanne Sattler; Ekaterina Semenova; Saveria Pastore; Teresa M. Kennedy-Lydon; Robert D. Sampson; Michael D. Schneider; Nadia Rosenthal; Daniel Bilbao (The Company of Biologists, 2014)
Allergic contact dermatitis (ACD) is triggered by an aberrant hyperinflammatory immune response to innocuous chemical compounds and ranks as the world's most prevalent occupational skin condition. Although a variety of immune effector cells are activated during ACD, regulatory T (Treg) cells are crucial in controlling the resulting inflammation. Insulin-like growth factor-1 (IGF-1) regulates cell proliferation and differentiation and accelerates wound healing and regeneration in several organs including the skin. Recently IGF-1 has also been implicated in protection from autoimmune inflammation by expansion of Treg cells. Here, we demonstrate that ectopic expression of IGF-1 in mouse skin suppresses ACD in a Treg cell-specific manner, increasing the number of Foxp3+ Treg cells in the affected area and stimulating lymphocyte production of the anti-inflammatory cytokine interleukin 10. Similar therapeutic effects can be achieved with systemic or topical delivery of IGF-1, implicating this growth factor as a promising new therapeutic option for the treatment of ACD.